KORELASI PEMBELAJARAN MATEMATIKA BERBASIS LITERASI NUMERASI TERHADAP PRESTASI BELAJAR SISWA KELAS VII SMP MIFTAHUS SA’ADAH TARUM KABUPATEN NGAWI TAHUN 2022 - Izzatul Choiru Nisa; Indra Puji Astuti; Restu Lusiana (Universitas Veteran Bangun Nusantara, 2023)
Many factors that affect learning achievement include intelligence, interest and attention, motivation to learn, learning mathematics based on numeracy literacy, perseverance, attitude, study habits, as well as physical and health conditions. Learning mathematics based on numeracy literacy is one of the important factors to improve learning achievement. This study aims to determine the relationship between mathematics learning based on numeracy literacy and student achievement. This research is a quantitative research using a survey method with a correlational approach. The sampling technique in this study used purposive sampling on all seventh grade students of SMP Miftahus Sa'adah Tarum. Data collection methods used in this study are tests, questionnaires, and documentation. The researcher uses the analysis prerequisite test, namely normality test, homogeneity test, linearity test and hypothesis testing, namely product moment correlation to analyze the data. The results showed that there was a positive relationship between mathematics learning based on numeracy literacy on the learning achievement of seventh grade students of SMP Miftahus Sa'adah Tarum, with r = 0.48 and tcount>ttable , namely 3.09 > 2.06.